THE EFFECT OF FINANCIAL RATIOS ON STOCK RETURNS IN TELECOMMUNICATIONS COMPANIES - Rinto Retnadi Fauzi; Nizwan Zukhri; Diki (Faculty of Economic and Business, University of Pasundan, 2021)
The purpose of this study was to analyze and investigate the effect of liquidity, solvency, and profitability on stock returns in telecommunications companies listed on the Indonesia Stock Exchange in 2010 - 2018. In this study, the measurement of liquidity ratio used the current ratio; the solvency ratio was measured using DAR (Debt to Asset Ratio) and DER (Debt to Equity Ratio), while the profitability ratio used ROA (Return on Asset Ratio) and ROE (Return on Equity Ratio). The results of this study indicate that liquidity which measured using current ratio had a negative but insignificant effect on stock returns, while solvency measured using DAR and DER, as well as profitability measured using ROA and ROE had a positive but insignificant effect on stock returns of telecommunications companies, respectively.